Enhancing charge mobilities in organic semiconductors by selective fluorination: a design approach based on a quantum mechanical perspective. Issue 10 (23rd August 2017) - Maiti, Buddhadev; Schubert, Alexander; Sarkar, Sunandan; Bhandari, Srijana; Wang, Kunlun; Li, Zhe; Geva, Eitan; Twieg, Robert J.; Dunietz, Barry D.
Abstract : Selective fluorination of organic semiconducting molecules can enhance attractive intermolecular interactions without increasing the risk for charge trapping. Abstract : Selective fluorination of organic semiconducting molecules is proposed as a means to achieving enhanced hole mobility. Naphthalene is examined here as a root molecular system with fluorination performed at various sites. Our quantum chemical calculations show that selective fluorination can enhance attractive intermolecular interactions while reducing charge trapping. Those observations suggest a design principle whereby fluorination is utilized for achieving high charge mobilities in the crystalline form. The utility of this design principle is demonstrated through an application to perylene, which is an important building block of organic semiconducting materials. We also show that a quantum mechanical perspective of nuclear degrees of freedom is crucial for a reliable description of charge transport.